(3GdGSJjYGH aj eYQaI GdCUMGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s ((3CMeO Hf eMeO Gdjefi s)
(3ChdgG (B:s
(3bGd HMeO Gddg CHJOi GdMeO ddg LGeY GdChdjf hGdBNQjf CeG HYO , aEf Chdi eG fXQ ajg GdWGdH hHYO heYdhe Cf ef Mce Hbhdg hbVi HTgGOJg adGHO ef eYQaI GSeg hfSHg hYOGdJg s
(3BNQgG (B:s
(3ef HGH ef GSeg YHO GdQMef , JQLeg YHO GdQMef Hf edA , bhdg (B: (3hcGf jUdi HfG UdGI GdUHM afhO dh bQC HGdHbQI ef MSf bQGAJg hbGd (B: (3ce YfO eYJeQ Yf CHjg (B'(3f CHj YKeGf KdJ eFI , bGd YfOi efgG NeShf fLR GdLRA GdChd ef cJGH GdESJjYGH hGdMeO ddgs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eVHhWs
(3ai GdeYgO fSNI CNQis
(3HQbe (B28 (3JGQjNs
(3ai JQGLe GdUMGHI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs